Diagnostic Approach, Treatment, and Outcomes of Cervical Sympathetic Chain Schwannomas: A Global Narrative Review. (December 2014) - Navaie, Maryam; Sharghi, Leighla H.; Cho-Reyes, Soojin; Keefe, Michael A.; Howie, Benjamin A.; Setzen, Gavin
Objective: This review examined the diagnostic approach, surgical treatment, and outcomes of cervical sympathetic chain schwannomas (CSCS) to guide clinical decision making. Data Sources: Medline, EMBASE, and Cochrane databases. Review Methods: A literature review from 1998 to 2013 identified 156 articles of which 51 representing 89 CSCS cases were evaluated in detail. Demographic, clinical, and outcomes data were extracted by 2 independent reviewers with high interrater reliability (κ = .79). Cases were mostly international (82%), predominantly from Asia (50%) and Europe (27%). Conclusions: On average, patients were 42.6 years old (SD = 13.3) and had a neck mass ranging between 2 to 4 cm (52.7%) or >4 cm (43.2%). Nearly 70% of cases were asymptomatic at presentation. Presurgical diagnosis relied on CT (63.4%), MRI (59.8%), or both (19.5%), supplemented by cytology (33.7%), which was nearly always inconclusive (96.7%). US-treated cases were significantly more likely to receive presurgical MRI than internationally treated cases but less likely to have cytology ( P < .05). Presurgical diagnosis was challenging, with only 11% confirmatory accuracy postsurgically. Irrespective of mass size, extracapsular resection (ie, complete resection with nerve sacrifice) was the most frequently (87.6%) performed surgical procedure. Common postsurgical adverse events included Horner's syndrome (91.1%), first bite syndrome (21.1%), or both (15.7%), with higher prevalence when mass size was >4 cm. Adverse events persisted in 82.3% of cases at an average 30.0 months (SD = 30.1) follow-up time. Implications for Practice: Given the typical CSCS patient is young and asymptomatic and the likelihood of persistent morbidity is high with standard surgical approaches, less invasive treatment options warrant consideration.